An analysis of Public Policies for the Comprehensive Protection of Victims of Violence - Silva, Fabiana Guadalupe Gálvez; Diaz, Marco Antonio Gálvez; Bartra, Martín Pinchi (Journal of Ecohumanism, 2024)
The article addresses the analysis of public policies to determine how effective they could be in protecting victims of violence. The research had a focus focused on violence against women. The seriousness of this social problem is highlighted, which deeply affects the victims, their families and society in general. This article had a qualitative approach, Basic Type and Grounded Theory Design. Given this problem of violence, the creation of Temporary Refuge Homes is mentioned as a crucial measure to provide comprehensive protection and support to survivors, thus emphasizing the signing of treaties and conventions to combat gender violence and discussing the implementation of policies such as the Aurora Program and the Women’s Emergency Centers to face this crisis. The importance of improving coordination between public and private institutions is highlighted to ensure adequate protection and care for victims. A comprehensive intervention is proposed that includes psychological support, legal assistance and skills development to promote the recovery and reintegration of victims.